2014
DOI: 10.1016/j.explore.2014.02.002
|View full text |Cite
|
Sign up to set email alerts
|

Brief Training of Psychoneuroendocrinoimmunology-Based Meditation (PNEIMED) Reduces Stress Symptom Ratings and Improves Control on Salivary Cortisol Secretion Under Basal and Stimulated Conditions

Abstract: Brief PNEIMED training yields immediate benefits, reducing distress symptoms and adrenocortical activity under basal and stimulated conditions. PNEIMED may represent an effective practice to manage stress and anxiety, particularly among subjects facing a multitude of job-related stressors, such as healthcare workers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 41 publications
0
10
0
1
Order By: Relevance
“…[103,192] Interventions during the perinatal period are the best way to strengthen the coping strategies and stress management for pregnant women with better outcomes. [103,159,191,193] Present study showed that EBMI may have effect on coping mechanism through improvement in positive appraisal as shown in Prenatal Coping Inventory in FP group at T2 when compared with control and Not FP group (p < .05) (see Table 6). Present intervention may be effective in promoting maternal health through improved stress-coping mechanism.…”
Section: Discussionmentioning
confidence: 56%
“…[103,192] Interventions during the perinatal period are the best way to strengthen the coping strategies and stress management for pregnant women with better outcomes. [103,159,191,193] Present study showed that EBMI may have effect on coping mechanism through improvement in positive appraisal as shown in Prenatal Coping Inventory in FP group at T2 when compared with control and Not FP group (p < .05) (see Table 6). Present intervention may be effective in promoting maternal health through improved stress-coping mechanism.…”
Section: Discussionmentioning
confidence: 56%
“…Dual diagnosis with concurrent treatment of PTSD and substance use disorder has demonstrated overall improvement in outcomes (Back, Waldrop, Brady, & Hien, 2006; Mills et al, 2012; Najavits, Weiss, Shaw, & Muenz, 1998), but broader application of stress amelioration techniques may be advantageous in this population. Mindfulness training, with or without integrated meditation, body relaxation, acupressure, or distress intolerance components, has shown stable decreases in subjective distress, basal cortisol, and the amplitude/duration of physiological reactivity to a stressor (cortisol response, heart rate), within healthy controls (Bottaccioli et al, 2014; Fan, Tang, & Posner, 2014) and tobacco (Davis, Manley, Goldberg, Smith, & Jorenby, 2014; Goldberg et al, 2014), cocaine (Brewer et al, 2009; Kevin W Chen, Berger, Gandhi, Weintraub, & Lejuez, 2013), or alcohol abuse (Stasiewicz et al, 2013) treatment cohorts. Increased abstinence behavior and decreased cravings have likewise resulted from mindfulness or neurofeedback (biofeedback focused on electroencephalograms, EEG) training in substance abuse treatment (Kevin W Chen et al, 2013; Goldberg et al, 2014; Ross, 2013; Stasiewicz et al, 2013), including opioid addiction (Dehghani-Arani, Rostami, & Nadali, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…There is evidence from both human and animal research that intensive stress may affect many aspects of the integrative network among the nervous, endocrine and immune systems . The complex effects of stress on the interactions among these systems have been subjected to studies in the developing field of psychoneuroendocrinoimmunology . Many studies have demonstrated that some degree of stress can affect the secretion of hormones, cytokines, immunoglobulins and many other proteins connected with the immune response .…”
Section: Introductionmentioning
confidence: 99%